IMPLEMENTASI PROSES PERIZINAN DAN PENGENDALIAN PEMANFAATAN RUANG MELALUI IZIN MENDIRIKAN BANGUNAN (IMB) DIKECAMATAN TIRAWUTA KABUPATEN KOLAKA TIMUR - Ilham, Ilham; Rianse, Usman; Yunusi, Lukman (EDUTECH CONSULTANT, 2019)
This study aims to determine and analyze; Implementation of procedures for the process of controlling spatial use through IMB; Conformity of building spatial planning (RDTR) policy towards IMB implementation; Factors that cause the suitability or incompatibility of spatial use through IMB to the spatial plan (RDTR); and Directions for the use of space in an effort to control spatial use through IMB in Tirawuta District. This type of research uses a qualitative approach to survey design. Regional samples are determined by census sampling, community samples are determined by sampling quota. Data were analyzed by descriptive qualitative and spatial analysis through a map overlay process. The results of the study concluded that the implementation of building management procedures through the issuance of IMB in controlling spatial use had been running